Coronavirus disease (COVID-19) pandemic visit COVID-19 site for news, technical guidance and protection advice [electronic resource] (WHO Regional Office for Europe, 2020)
COVID-19 is an emerging, rapidly evolving situation. Get the latest public health information from this site.